Extended visual cryptography for continuous–tone images: effect of the optimum tone mapping. (1st December 2014) - Yamaguchi, Yasushi
Visual cryptography is a kind of cryptography that can be decrypted only by a human visual system when stacking transparencies. Extended visual cryptography allows to print meaningful images on transparencies which can conceal the existence of 'secret' in the transparencies. Many studies have tried to incorporate continuous–tone images into extended visual cryptography. However, most of them failed in preserving the image quality after the encryption. This paper introduces a scheme for extended visual cryptography for continuous–tone images. The scheme is based on parallel error diffusion that can quickly encrypt images with no pixel expansion. The most important feature of this scheme is the optimum tone mapping so that the resulting images may have very high contrast comparing with the conventional schemes. Some experimental results are shown to evaluate the effectiveness of the optimum tone mapping.